2021
DOI: 10.1371/journal.pone.0246044
|View full text |Cite
|
Sign up to set email alerts
|

Modeling vehicle ownership with machine learning techniques in the Greater Tamale Area, Ghana

Abstract: Vehicle ownership modeling and prediction is a crucial task in the transportation planning processes which, traditionally, uses statistical models in the modeling process. However, with the advancement in computing power of computers and Artificial Intelligence, Machine Learning (ML) algorithms are becoming an alternative or a complement to the statistical models in modeling the transportation planning processes. Although the application of ML algorithms to the transportation planning processes—like mode choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Public management influences car ownership, as in the case of public transportation. Depending on the quality of public transport and access to critical services, the need to own a car intensifies ( 41 , 49 ). In Ghana, for example, public transportation is characterized by low-quality services, thus reinforcing car ownership ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Public management influences car ownership, as in the case of public transportation. Depending on the quality of public transport and access to critical services, the need to own a car intensifies ( 41 , 49 ). In Ghana, for example, public transportation is characterized by low-quality services, thus reinforcing car ownership ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the quality of public transport and access to critical services, the need to own a car intensifies ( 41 , 49 ). In Ghana, for example, public transportation is characterized by low-quality services, thus reinforcing car ownership ( 49 ). Accessibility to public transport is low in Australia because of its low population density, which reinforces the dependence on private cars ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, several studies have employed ML algorithms to predict the HVO (e.g., [6,36,[41][42][43][44][45]). Table 1 shows a summary of these studies.…”
Section: Methods Used For Hvo Predictionmentioning
confidence: 99%
“…The support vector machine (SVM) algorithm was employed in several studies to analyze vehicle ownership and showed promising performance [41,42,46]. Abdul Muhsin Zambang, Jiang, and Wahab [42] compared the performance of SVM with other ML techniques in Greater Tamale. However, their study did not employ any algorithm to optimize the SVM or other techniques' hyperparameters.…”
Section: Methods Used For Hvo Predictionmentioning
confidence: 99%
“…The work in [396] models vehicle ownership in the Greater Tamale Area, Ghana, utilizing machine learning techniques.…”
Section: Côte D'ivoirementioning
confidence: 99%